Edukasi Pemanfaatan Sampah Anorganik menjadi Ecobrick sebagai Upaya Pengurangan Sampah Plastik - Yulius Evan Christian, Yulius Evan Christian; Christian, Yulius Evan (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
Plastic waste is considered one of the major problems worldwide due to its non-biodegradable nature. Inorganic waste, especially plastic, has become an increasingly urgent environmental problem to address. This community service aims to introduce the concept of ecobricks as a creative solution for managing inorganic waste. Through active community participation, ecobricks are created in an effort to reduce the negative impact of plastic waste on the environment. This community service method includes education, training, and implementation stages. Training to teach villagers how to identify, sort, clean, and package plastic waste into sturdy ecobricks. Based on the results of the service, it shows an increase in community awareness of the importance of inorganic waste processing. The success of this activity can be seen from the level of community understanding of ecobricks before (37.4%) and after (90.4%) the implementation of socialization activities. Community understanding of ecobricks is increasing. Based on statistical analysis, by filling out pretest and posttest questions, the p value is 0.007( <0.05), so it can be concluded that there is a significant difference between before and after the activity.